Título del libro: Hyperthinking. Creating a new mindset for the age of networks - Cano, Jannet (Review of Global Management, 2018)
Reseña del libro "Hyperthinking. Creating a new mindset for the age of networks", del autor Philip Weiss, publicado el año  2012.